Two new species of Heterophrynus Pocock, 1894 from Colombia with distribution notes and a new synonymy (Arachnida: Amblypygi: Phrynidae) - Giupponi, Alessandro P. L.; Kury, Adriano B. (Zootaxa, 2013)
The genus Heterophrynus is for the first time recorded from Transandean areas. Heterophrynus boterorum sp. nov. and Heterophrynus silviae sp. nov. are described respectively from Tolima and Valle del Cauca departments, Colombia, based on material from the 2006 Arachnological Expedition of Museu Nacional to Colombia. Heterophrynus nicefori Amado & Morales, 1986, from Meta department is newly considered a junior subjective synonym of Phrynus batesii Butler, 1873 (currently in Heterophrynus). Heterophrynus is currently known from Amazon forest, Brazilian Cerrado, Littoral Ridge of Venezuela and Andean forests. A revised terminology is proposed for the constituent parts of male and female gonopods of Heterophrynus.